Organizational Justice Is Related to Heart Rate Variability in White-Collar Workers, but Not in Blue-Collar Workers—Findings from a Cross-Sectional Study. Issue 3 (4th December 2014) - Herr, Raphael M.; Bosch, Jos A.; van Vianen, Annelies E. M.; Jarczok, Marc N.; Thayer, Julian F.; Li, Jian; Schmidt, Burkhard; Fischer, Joachim E.; Loerbroks, Adrian
Abstract: Background: Perceived injustice at work predicts coronary heart disease. Vagal dysregulation represents a potential psychobiological pathway. Purpose: We examined associations between organizational justice and heart rate variability (HRV) indicators. Grounded in social exchange and psychological contract theory, we tested predictions that these associations are more pronounced among white-collar than among blue-collar workers. Methods: Cross-sectional data from 222 blue-collar and 179 white-collar men were used. Interactional and procedural justice were measured by questionnaire. Ambulatory HRV was assessed across 24 h. Standardized regression coefficients ( β ) were calculated. Results: Among white-collar workers, interactional justice showed positive relationships with 24-h HRV, which were strongest during sleeping time (adjusted β s ≥0.26; p values ≤0.01). No associations were found for blue-collar workers. A comparable but attenuated pattern was observed for procedural justice. Conclusions: Both dimensions of organizational injustice were associated with lowered HRV among white-collar workers. The impact of justice and possibly its association with health seems to differ by occupational groups.